ChemInform Abstract: Syntheses, Structures and Properties of Two New 3‐D Vanadoborates Based on V—O—B Clusters. Issue 38 (September 2016) - Tang, Qiuling; Zhou, Jian; Zou, Hua‐Hong; Tan, Xiao‐Feng
Abstract: (H3 O)4 { [Cd(H2 O)2 ]3 V12 B18 O54 (OH)6 }·26H2 O (I) and [K6 (H2 O)10 Zn4 V10 B32 O74 (OH)10 ]·5H2 O (II) are prepared by hydrothermal reaction of a 0.7:9.9:0.2 molar mixture of V(acac)3, H3 BO3, and Cd(O‐Ac)2 respectively a 0.7:10:0.25:2 molar mixture of NH4 VO3, H3 BO3, Zn(O‐Ac)2, and K2 SO3 (aq.